(untitled) (Samsad Journal संसद जर्नल, 2025)
The transition to federal governance in Nepal has presented numerous challenges, requiring comprehensive structural and procedural reforms within the Federal Parliament Secretariat. This research provides an extensive examination of key reform areas, including legislative processes, capacity building, public engagement, oversight mechanisms, administrative restructuring, and research development. Employing a qualitative approach, this study undertakes an in-depth analysis of existing governance gaps and presents well-researched, actionable recommendations. The findings underscore the significance of defining clear jurisdictional responsibilities, fostering robust stakeholder engagement, and enhancing institutional capacity to ensure the effective and efficient functioning of the Federal Parliament Secretariat. By implementing these essential reforms, Nepal’s parliamentary governance can evolve to become more transparent, accountable, and proficient in executing legislative functions, thereby strengthening democracy and promoting good governance practices in the country. This research fills a critical gap in the existing literature by providing a context-specific analysis of the Federal Parliament Secretariat and offering practical recommendations for its improvement.